Applying emotional intelligence skills to leadership and decision making in non-profit organizations - James D. Hess; Arnold C. Bacigalupo (Administrative Sciences, 2013)
Non-profit organizations and leaders may benefit from the utilization of behaviors attributed to emotional intelligence. The consideration of emotional intelligence skills becomes a strategy for the development of the non-profit organizational leader's ability to assess the impact and consequences of decisions, while simultaneously improving the quality and effectiveness of the decision-making process. The purpose of this paper is to identify how emotional intelligence skills can be applied to enhance the leadership decision-making processes within the non-profit organization. Goleman's (2001) and Boyatzis' et al. (2000) four essential elements of emotional intelligence and their associated 20 behavioral competencies are utilized to develop a methodology for the practical application of emotional intelligence skills to leadership decision-making within the non-profit organization. A checklist of questions and observations is provided to assist non-profit leaders in the improvement of emotional intelligence awareness, as well as the application of emotional intelligence skills to decisions and decision-making processes.
Keywords: 350; non-profit organization; leadership; emotional intelligence; decision-making